Why are glucocorticoids recommended at a high dose in the Takayasu arteritis guidelines? - Kenar Artın, Gökçe (Acta Medica, 2024)
Takayasu arteritis is one the large vessel vasculitis affecting the aorta and major branches. Glucocorticoid treatment plays an important role in the treatment of this disease, as in all vasculitis.According to the most recent evidence, theguidelines suggested initiating GCs at high dosages, particularly in patients who had just received a diagnosis. This review aims to analyze this research and identify the rationale behind the current guidelines’ recommendations.